ANALISIS PEMASARAN TOMAT DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Desi Saputri; Made Antara; Karlina Muhsin Tondi (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The aim of this research was (i) to identify the marketing channels and margins of tomato marketing, and (ii) to determine the level of efficiency and prices received at the farm level in Labuan Toposo village, Labuan sub district of Donggala district. It was conducted in March to April 2020. The farmer respondents of 47 people were selected using the census method, ensuring that all people in the population had an equal opportunity to be sampled. The merchant respondents were selected using the snowball method, involving six traders. The analysis used in the study included Marketing Margin analysis, Marketing Efficiency analysis, and Farmers Share analysis. The results of the study revealed that there were two tomato marketing channels in Labuan Toposo village: (i) farmers – collector traders – wholesalers – retailer – consumers, and (ii) farmer – wholesalers – retailers – consumers. The marketing margin was IDR 6,000 with 1.33% efficiency for the first channel and IDR 4,000 with 3.18% efficiency for the second channel. The share of prices received by the farmers in the first channel was 50%, while in the second channel was 66%.